2022
DOI: 10.1038/s41598-022-12273-7
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of serum adiponectin levels and bone mineral density in postmenopausal women in Taiwan

Abstract: Since bone and fat mass are derived from mesenchyme in early development, adipokines secreted by adipose tissue may have an effect on bone metabolism. The relationship between adiponectin and bone mineral density (BMD) has been inconsistent in previous reports, with results being dependent on age, gender, menopausal status and bone sites. We investigated the relationship between serum adiponectin levels and the BMD of proximal femur and vertebrae bones in a 96-week longitudinal study of post-menopausal women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Taken together, our findings of lower baseline adiponectin levels in progressors to prediabetes versus nonprogressors, an inverse correlation between adiponectin and BMD, and a positive association between BMD and incident prediabetes, implicate adiponectin as a possible mediator of the link between BMD and prediabetes risk. Previous reports have also shown a negative correlation between adiponectin and BMD ( 32 , 33 ). The mechanisms underlying the negative association between adiponectin and BMD are unclear, but increased bone marrow adipogenesis with associated increase in adiponectin production has been proposed to mediate decreased BMD ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 56%
“…Taken together, our findings of lower baseline adiponectin levels in progressors to prediabetes versus nonprogressors, an inverse correlation between adiponectin and BMD, and a positive association between BMD and incident prediabetes, implicate adiponectin as a possible mediator of the link between BMD and prediabetes risk. Previous reports have also shown a negative correlation between adiponectin and BMD ( 32 , 33 ). The mechanisms underlying the negative association between adiponectin and BMD are unclear, but increased bone marrow adipogenesis with associated increase in adiponectin production has been proposed to mediate decreased BMD ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 56%
“…This study reports a significant association between total adiponectin and the BMD of the lumbar spine, right femur, and left femur. Previous studies have also reported an association between adiponectin and the lumbar spine but not the femurs, nor all three [ 28 , 29 , 30 , 31 ]. Another study reported that increasing levels of adiponectin and lower BMD levels were positively associated with osteocalcin, a biomarker of bone resorption [ 44 ].…”
Section: Discussionmentioning
confidence: 93%
“…Adiponectin stimulates the osteoclast bone-resorbing RANK pathway [ 24 , 25 ]. Clinical studies report a negative correlation between circulating total adiponectin levels and the BMD of various skeletal sites [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several of the reviewed studies suggested that insulin levels might partially mediate the positive association between DM2 and increased BMD [ 33 35 ]. Individuals with DM2 typically exhibit an excess of insulin.…”
Section: Discussionmentioning
confidence: 99%